Paleo-Water Column Structure In The South Pacific: Evidence from Foraminiferal δ18O and Mg/Ca - Tapia Arroyo, Raúl Iván (2016)
The South Pacific represents the largest sector of the Southern Ocean. Here lies the major intermediate and bottom water formation region, rendering it a key area for studies of intermediate-deep water masses such as Subantarctic Mode Water (SAMW) and Antarctic Intermediate Water (AAIW). The intermediate waters formed in the Southern Ocean (e.g. AAIW and SAMW) sequester significant quantities of anthropogenic CO2 and other atmospheric gases in the ocean interior. These processes have been suggested to play an important role in modulating climatic variability at glacial-interglacial time scales. The AAIW and SAMW ventilate the thermocline of the oceanic gyres as well as form the link between the Southern Ocean and the tropics, via mechanisms such as “oceanic tunneling” that transport climatic signals (e.g. temperature and salinity) and nutrients across latitudes. The active participation of the AAIW and SAMW in the heat, freshwater and carbon transports at global scale renders their role relevant in climate modulation. The central South Pacific is still poorly understood, as previous paleoceanographic reconstructions are mostly limited to the outer rim of the SPG, i.e. equatorial Pacific or close to the continental margin of South America and New Zealand. In addition, a limit in temporal coverage is evident since a large number of the reconstructions in the domain of the SPG are either time slices (Holocene-Last Glacial Maximum), or not extending beyond ~100 kyr. Therefore, the climatic history of the central South Pacific prior to MIS 5 is virtually unknown. Despite the large volume of intermediate waters formed in the South Pacific and the extensive area that the SPG covers, information regarding past changes in the formation of AAIW-SAMW and its impact on the South Pacific Gyre (SPG)’s thermocline is basically absent Der Südpazifik repräsentiert den größten Teil des Südozeans. Hier befinden sich die bedeutendsten Intermediäre- und Tiefwasser Bildungsregionen, was dies zu einem Schlüsselgebiet dient um ...